GAMBARAN PENGETAHUAN WANITA MENOPAUSE TENTANG AKTIVITAS SEKSUAL - Eka Sarofah Ningsih (Jurnal MIDPRO, 2018)
Menopause is problem health reproduction on elderly especially in Indonesia. Many women argue that sexual intercourse can not be done again during menopause. Sexual intercourse remains to be done even in the elderly. But based on the momentary observation in the village of Wanar Kec.Pucuk Kab. Lamongan many women menopause who did not have sexual intercourse (14%). The purpose of this study is to know the description of knowledge of menopausal women about sexual activity in Wanar village, Pucuk sub-district, Lamongan regency.The research design used was descriptive survey with non probility sampling technique in total sampling. Population and sample counted 48 data collected by questioner then analyzed descriptively.Research result shows mostly knowledge of postmenopausal women about adequate sexual activity 52.1%, knowledge of postmenopausal women about good sexual activity 27.1%, and knowledge of menopausal women about sexual acvity less 20.8%.The conclusion of this study is that more than half of menopausal women have sufficient knowledge so as follow-up from health workers should provide education to menopausal women about sexual activity during menopauseKeywords: Knowledge, Menopause, Sexual activity